(untitled) (Web of Teachers: Inderscience Research, 2025)
The article considers the issues of organizing inclusive work, labor management, division of labor, proper organization of workplaces and work, labor planning, formation of labor discipline, as well as the importance of labor standards in the organization of labor. This includes consideration of the possibility of active participation in the labor market of people with disabilities, low-income groups and other social groups. The situations mentioned in the article are considered in general terms, and by taking anti-discrimination measures against social groups and creating an environment of equality among employees, each person and organization contributes to the creation of a just society. If you are interested in labor management, sociology and economics, this article is for you.